2008
DOI: 10.1089/apc.2007.0031
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Initiation of HIV Postexposure Prophylaxis in Rhode Island Emergency Departments

Abstract: The objective of this study was to elucidate factors that predicted the initiation of HIV postexposure prophylaxis (PEP) for blood or body fluid exposures evaluated at Rhode Island emergency departments (EDs). The study involved a retrospective review of patient visits to all civilian Rhode Island EDs for these exposures from 1995 to mid-2001. Multivariate logistic regression models were created to evaluate predictors of the offering and the acceptance and receipt of HIV PEP from 1996 to 2001. The search ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(19 reference statements)
0
9
1
Order By: Relevance
“…The differences between what we observed among PCPs sampled compared with HIV specialists were likely attributed to the general clinical context of nPEP initiations. For instance, nPEP is often initiated during emergency care for incidences of sexual assault (Merchant et al, 2003; Krause et al, 2014; Merchant et al, 2008). Most PCPs in our sample did not practice in emergency care settings and were not likely to encounter such types of urgent clinical situation, whereas HIV specialists might be called upon by emergency care providers to provide expert consultation regarding nPEP.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between what we observed among PCPs sampled compared with HIV specialists were likely attributed to the general clinical context of nPEP initiations. For instance, nPEP is often initiated during emergency care for incidences of sexual assault (Merchant et al, 2003; Krause et al, 2014; Merchant et al, 2008). Most PCPs in our sample did not practice in emergency care settings and were not likely to encounter such types of urgent clinical situation, whereas HIV specialists might be called upon by emergency care providers to provide expert consultation regarding nPEP.…”
Section: Discussionmentioning
confidence: 99%
“…BBVs can also be found in body fluids other than blood, such as, semen, vaginal secretions and breast milk. BBVs constitute a major occupational hazard for healthcare workers (HCW), especially in highly resource constrained countries [2]. …”
Section: Introductionmentioning
confidence: 99%
“…12 When evaluating PEP from the perspective of cases as opposed to provider-based data, a retrospective analysis of Rhode Island EDs in 2008 showed that only 21% of eligible cases had PEP offered, and it was more likely in scenarios with health care workers in the occupational setting. 13 Considering the above-mentioned data, our finding that 88% (n ¼ 161 of 184) of NYS EDs reported evaluating any presenting patient with possible nonoccupational exposure for HIV suggests that the use of nPEP is relatively robust in NYS. This practice is likely due to long-standing efforts of the NYS Department of Health AIDS Institute to promote its use through community education and the Clinical Education Initiative.…”
Section: Discussionmentioning
confidence: 80%
“…12 When evaluating PEP from the perspective of cases as opposed to provider-based data, a retrospective analysis of Rhode Island EDs in 2008 showed that only 21% of eligible cases had PEP offered, and it was more likely in scenarios with health care workers in the occupational setting. 13…”
Section: Discussionmentioning
confidence: 99%